Moral Dilemma Debates with Older Persons - de Souza, Luciana Karine; Martínez, Sophia Beylouni Santos; Pereira, Milene Amaral; Fritzen, Bruna Wagner; Bataglia, Patrícia Unger Raphael [UNESP]; Gauer, Gustavo (Editorial Pontificia Universidad Javeriana, 2023)
This research study and educational intervention aimed to foster ethical reasoning in older persons via systematic debates on moral dilemmas. We conducted an intervention via focus group with seven participants aged between 60 e 82 years old (six women and one man), all residing in Porto Alegre, Brazil. They participated in a 15-week intervention with 13 moral dilemma discussions. The first and the last group meeting were used for assessment (pre-test and post-test), with the Moral Competence Test and other measures. We gathered enough evidence that the intervention yielded positive results that fostered continued reflection on complex topics and the exercise of individual and group critical thinking. Results shed light on how moral competence, moral development after the age of 60, and universal and culture-specific moral issues are intertwined. This program has been requested to be offered regularly at the university.
Debates de Dilemas Morales con adultos mayores
Keywords: anciano; desarrollo; development; dilema; dilemma; discusión moral; intervención; intervention; moral discussion; older person